The Design Of Project Risk Management To Mitigate Project Delay In the Onshore Construction Industry (Case: Shore Protection Project)CTION INDUSTRY (CASE: SHORE PROTECTION PROJECT) - Muhammad, Firdaus Yusri; Yudoko, Gatot; Hanafi, Muhammad (Politeknik Siber Cerdika Internasional, 2025)
This study aims to design a project risk management system to mitigate delays in the land-based construction industry, using a case study of the PT Sabar Sejahtera coastal protection project. The project experienced a three-month delay, resulting in financial losses and lost business opportunities due to a lump-sum contract. The methods employed included both qualitative and quantitative approaches, with primary data collected through focus group discussions with project stakeholders and secondary data sourced from internal company documents. Root cause analysis used a Current Reality Tree (CRT) to identify the causes of delays, while solutions were visualized through a Future Reality Tree (FRT). Risk evaluation was conducted using a Failure Mode and Effects Analysis (FMEA) to calculate the Risk Priority Number (RPN), as well as the application of a risk management framework based on the PMBOK 6th Edition. The results showed that the leading causes of delays were systematic errors at the tendering and planning stages, as well as the unavailability of a risk mitigation plan. These two factors caused a domino effect on procurement, equipment, schedules, and the confidence of the main contractor. Proposed solutions included improving the tendering and planning system by involving various departments early and implementing the complete PMBOK risk management cycle. The implications of this study highlight the importance of a structured risk management system in preventing similar project delays in the future. This study also provides strategic guidance for improving the efficiency and control of construction projects in complex work environments.